Assessing the quality of services provided at outpatient clinics among hospitals affiliated to Tehran University of Medical Sciences based on SERVQUAL Model in 2015 - Elham Haghshenas; Mohammad Arab; Abass Rahimi; Elham Movahed (Tehran University of Medical Sciences, 2017)
Background: The quality of services is a comparison of the customer´s perspective (expectations) with what it has received. If the expectations are more than perceptions, the quality of received services is not sufficient based on customer´s view which resulted in his/her dissatisfaction. The present study performed with the purpose of determining the quality of provided and excepted services to outpatients among hospitals affiliated to Tehran University of Medical Sciences. Material and Methods: The present study is a descriptive- analytics and cross sectional one which has been done in 2015. The study population included all outpatients attending hospital clinics affiliated to Tehran University of Medical Sciences.The sample size was calculated 225 participants based on formula. In order to data gathering in quality of provided and expected services, a 22-items standard questionnaire of Servqual was utilized. Data analysis performed by SPSS using paired t-test, Mann-Whitney and Kruskal-Wallis tests. Results: The study findings represented that there was a negative gap in the quality of services provided. The highest gap was related to accountability (-0.97) and the lowest gap related to tangibles factors (-0.69) .Moreover, regarding to  relationship between demographic variables with perceived service quality, there were significant relationship between  insurance type with reliability and empathy dimensions and supplementary insurance with tangibles factors and reliability. Conclusion: Negative gap (higher expectations than perception) in all aspects of quality improvement is required in all dimensions. Especially, it is necessary to adopt some strategies in the accountability dimension. Reforming management processes, reducing waiting times and increasing employeeschr('39') motivation in order to achieve appropriate accountability are in this kind of strategies.